Post a New Question

math

posted by on .

solve using substitution

3x-4y=-5
x=y+2
HELP Me.!

  • math - ,

    This one is easy. x is already expressed in terms of y in the second equation. You only have to replace the x in the forst equation with the expression from the second equation. You get that:

    3*(y+2)-4y=-5
    =>3y+6-4y=-5
    =>6-y=-5
    =>y=11

    When we place this value for y in the second equation, we find that

    x=11+2=13

    So, y=11 and x=13

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question